PENGARUH MOTIF DALAM PENGGUNAAN MEDIA SOSIAL INSTAGRAM @IAMOKAY.ID TERHADAP PEMENUHAN KEBUTUHAN INFORMASI KESEHATAN MENTAL: Survei Pada Followers Aktif Akun Instagram @iamokay.id - Dyandra Putri Divianti, (2022)
The development of information technology greatly affects human life, especially with the emergence of new media. In the current digital era, the new media that is widely used by the public is social media. The existence of social media can create interaction between individuals, especially social media Instagram. I Am Okay, one of the social organizations that uses Instagram as a medium to share mental health information. I Am Okay seeks to help young people in Indonesia raise awareness about the importance of mental health through photo or video content management programs, education, and outreach. This study discusses the use of social media, especially Instagram which aims to determine whether or not the use of social media Instagram @iamokay.id mediates the relationship between motives for using media to fulfill mental health information needs. This research uses an explanative type of quantitative approach. The survey method researchers used to distribute questionnaires to the respondents included 100 Instagram followers on Instagram @iamokay.id with the purposive sampling technique. The theory used in this research is Uses and Gratification Theory. The Uses and Gratification theory model is based on four (4) things, namely antecedents, motives, use of media, and effects. Data analysis used classical assumption test calculations, correlation test, coefficient of determination test, multiple regression effect test and path analysis because there were mediating variables, and hypothesis testing with T test and Sobel test. Based on the results of calculations and hypothesis testing, it was found that H0 was rejected and Ha was accepted. The conclusion obtained is that the significant use of social media Instagram @iamokay.id is able to mediate the relationship between the influence of usage motives on the fulfillment of mental health information needs with a Z count of 5.8750004 and the results of the study are able to confirm the Uses and Gratification theory related to media use. Future research is expected to find other variables that support the development of the Uses and Gratification Theory.